2011
DOI: 10.1016/j.bbrc.2011.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Plural assay systems derived from different cell lines and hepatitis C virus strains are required for the objective evaluation of anti-hepatitis C virus reagents

Abstract: Persistent hepatitis C virus (HCV) infection causes chronic liver diseases and is a global health problem. HuH-7 hepatoma-derived cells are widely used as the only cell-based HCV replication system for HCV research, including drug assays. Recently, using different hepatoma Li23-derived cells, we developed an HCV drug assay system (ORL8), in which the genome-length HCV RNA (O strain of genotype 1b) encoding renilla luciferase replicates efficiently. In this study, using the HuH-7-derived OR6 assay system that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…This finding led us to clarify the anti-HCV mechanism of RBV [22], [23]. Furthermore, we demonstrated that plural assay systems including OR6 and ORL8 were required for the objective evaluation of anti-HCV reagents [24]. In that study, we observed that the antimalarial drug artemisinin possessed weak anti-HCV activity, as reported previously [25].…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…This finding led us to clarify the anti-HCV mechanism of RBV [22], [23]. Furthermore, we demonstrated that plural assay systems including OR6 and ORL8 were required for the objective evaluation of anti-HCV reagents [24]. In that study, we observed that the antimalarial drug artemisinin possessed weak anti-HCV activity, as reported previously [25].…”
Section: Introductionsupporting
confidence: 75%
“…Recently we demonstrated that plural HCV assay systems developed using both HuH-7 and Li23 cell lines or HCV strains belonging to genotype 1b are required for the objective evaluation of anti-HCV candidates [24]. In the present work, we used our previously developed HCV assay systems to evaluate preclinical antimalarial drugs (N-89 and N-251).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AB191333)-replicating cell lines, OL (polyclonal; a mixture of approximately 200 clones), OL8 (monoclonal), OL11 (monoclonal), and OL14 (monoclonal) [21], and have been culturing them for more than 4 years. Since we demonstrated that the gene expression profile of Li23 cells was distinct from those in HuH-7 cells [22], and that anti-HCV targets in Li23-derived cells were distinct from those in HuH-7-derived cells [23][25], we expected to find distinct HCV variability and diversity from those observed previously in HuH-7-derived cells. To clarify this point, we carried out comprehensive genetic analysis of HCVs obtained from 0-year, 2-year, and 4-year cultures of OL, OL8, OL11, and OL14 cells, and compared them with the original ON/C-5B/QR,KE,SR RNA [21].…”
Section: Introductionmentioning
confidence: 81%
“…Ueda et al reported that 6-azauridine showed anti-HCV activity in an HCV drug assay system (ORL8), and the selective index from dividing the CC 50 value by the EC 50 value was 4.1 [48].…”
Section: Discussionmentioning
confidence: 99%